Sub Rosa - Dawn, Amber (XYZ éditeur, 2019)
Les filles sont bien traitées, rue Sub Rosa. Elles n’ont jamais faim, jamais froid, jamais mal. Elles sont entre de bonnes mains, des mains qui leur tendent tout ce dont elles ont besoin… à une condition. Il faut accepter de combler les désirs des hommes de la ville venus faire un tour dans ce lieu surnaturel, caché, où leurs fantasmes deviennent réalité – pourvu, bien sûr, qu’ils aient un peu d’argent sur eux. Petite a tout pour se tailler une place de choix parmi les Splendides de Sub Rosa. Mais parviendra-t-elle à oublier sa vie d’avant et à exploiter son don au service de sa nouvelle maison?
Keywords: adolescence; approches et analyses; arts; corps; discipline; inégalités; patriarcat; roman; sexisme; systèmes d'oppressions; thématiques; travail; travail du sexe-prostitution; violences; études littéraires

La charge émotionnelle et autres trucs invisibles - Emma (Un autre regard, 2019)
Par la blogueuse Emmaclit et autrice d'Un autre regard 1 et 2. Dans ce nouvel ouvrage, Emma aborde des sujets de société qui l'interpellent comme la charge émotionnelle, le consentement, les violences du système policier, les grèves, la charge mentale professionnelle...? " Je lis plein de choses et je les regroupe par thèmes. Au bout d'un moment, j'ai le sentiment qu'un des thèmes mérite d'être porté au public. Je résume et ancre ce thème un peu théorique dans nos vies privées : ces expériences personnelles qui permettent de toucher chaque femme. C'est vraiment ça que j'ai vécu quand je me suis éveillée à la politique, qui a longtemps été pour moi un truc un peu chiant. J'ai trouvé dans des articles féministes des scènes que j'avais vécues. Il n'était pas possible que ce soit arrivé à plein de femmes, même à l'autre bout du monde, et qu'il n'y ait pas de lien ! J'ai ensuite lu des articles expliquant ce qui fait que des catégories de personnes vivent des choses similaires : il existe un système. Partir de ces événements que l'on vit seule, montrer qu'on les vit toutes, et faire apparaître l'importance du contexte : de cette façon, on peut agir sur le contexte pour changer son expérience personnelle. "
Keywords: 2000 à aujourd'hui; approches et analyses; bande-dessinée; charge mentale; charge émotionnelle; humour; patriarcat; projet charge mentale; périodes historiques; systèmes d'oppressions; thématiques; travail; travail invisible; violences

Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis

La charge mentale, une source d’épuisement, - Lanteigne, Amélie (RQASF, 2019)
De nombreuses femmes se sentent surchargées mentalement, et avec raison. La charge mentale de plus en plus lourde que les femmes ressentent au quotidien est le fruit d’une accumulation de responsabilités multiples, qui dépasse largement le fait d’entretenir la maison et de s’occuper des enfants. Lorsque la charge mentale est trop grande, des problèmes psychologiques peuvent se manifester. Troubles anxieux, épuisement professionnel, dépression : l’épuisement au féminin est un phénomène de plus en plus répandu.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; charge mentale; conciliation famille-travail; famille; inégalités; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; santé des femmes*; systèmes d'oppressions; thématiques; travail

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible